Intake, gain and carcass traits of Hereford and Charolais bulls offered diets based on triticale, barley and grass silages - Huuskonen, Arto; Jaakkola, Seija; Manni, Katariina (Scientific Agricultural Society of Finland, 2020)
Total mixed rations (TMR) based on grass silage (GS), triticale silage (TS), mixture of GS and TS, barley silage (BS) and mixture of GS and BS were fed to fifty Hereford (HF) and fifty Charolais (CH) bulls. The proportion (g kg-1 dry matter [DM]) of the silages in the TMRs were as follows: (1) GS (600); (2) TS (600); (3) GS (300) and TS (300); (4) BS (600); (5) GS (300) and BS (300). Concentrate proportion was 400 g kg-1 DM. According to feed analyses, the GS had 15 and 8% higher metabolizable energy (ME) concentration as well as 51 and 49% higher crude protein (CP) concentration compared to TS and BS, respectively. Average DM intake (DMI) on TS and BS containing diets was higher compared to GS as a sole forage (p=0.001). Compared to the TS based rations the use of BS rations increased daily DMI by 5% (p<0.05). In CH bulls, DMI decreased 0.8 kg d-1when GS partially replaced TS or BS while in HF bulls the use of silage mixtures slightly increased DMI (0.23 kg d-1). The live weight gain (LWG) and carcass gain of the CH bulls were 5 and 26% higher, respectively, compared to the HF bulls. Inclusion of GS in the diet increased LWG and carcass gain with TS but decreased them with BS (interaction p<0.01). The experiment demonstrated lower feeding value of TS compared to BS in the diet of the bulls. Whole crop silage based rations increased DMI compared to GS as a sole forage in the TMR. When GS partially replaced TS or BS, interactions in LWG and carcass gain results demonstrated higher feeding value for BS and lower for TS compared to GS. Feeding treatments had only minor effects on carcass traits of the bulls.
Keywords: beef production; growth performance; Hordeum vulgare; timothy-grass; whole crop silages; X Triticosecale